2005
DOI: 10.1002/pmic.200300938
|View full text |Cite
|
Sign up to set email alerts
|

Lipoproteomics I: Mapping of proteins in low-density lipoprotein using two-dimensional gel electrophoresis and mass spectrometry

Abstract: The molecular mechanisms underlying the relationship between low-density lipoprotein (LDL) and the risk of atherosclerosis are not clear. Therefore, detailed information about the protein composition of LDL may contribute to reveal its role in atherogenesis and the mechanisms that lead to coronary disease in humans. Here, we sought to map the proteins in human LDL by a proteomic approach. LDL was isolated by two-step discontinuous density-gradient ultracentrifugation and the proteins were separated with two-di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
129
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(142 citation statements)
references
References 46 publications
13
129
0
Order By: Relevance
“…Novel proteins were identified in HDL by these approaches. Also using 2-DE and the new MS technologies, Karlsson et al [100] studied the protein content of LDL, and identified calgranulin and lysozyme C in these lipoproteins. Their observation raises the possibility of new links between lipid metabolism, immunity and inflammation, which may be of relevance in the context of atherosclerosis.…”
Section: Lipidomicsmentioning
confidence: 99%
“…Novel proteins were identified in HDL by these approaches. Also using 2-DE and the new MS technologies, Karlsson et al [100] studied the protein content of LDL, and identified calgranulin and lysozyme C in these lipoproteins. Their observation raises the possibility of new links between lipid metabolism, immunity and inflammation, which may be of relevance in the context of atherosclerosis.…”
Section: Lipidomicsmentioning
confidence: 99%
“…The identities of the proteins attached to HDL, LDL, and VLDL have recently been analyzed using proteomics (10)(11)(12)(13)(14)(15)(16). In particular, the list of proteins believed to be associated with HDL particles has grown significantly in recent years (17).…”
Section: White) (D and E)mentioning
confidence: 99%
“…Many lines of evidence strongly link them to the immune system and macrophage biology (91)(92)(93) . Several approaches have been developed for lipoprotein isolation (94)(95)(96)(97) ; delipidation (98,99) ; sample preparation (solubilisation and digestion) (100)(101)(102)(103) ; and the characterisation of protein component of lipoproteins using MS (104,105) .…”
Section: Analysis Of Post-translational Modificationsmentioning
confidence: 99%